Weather variability and extreme shocks in Africa: Are female or male farmers more affected? - Azzarri, Carlo; Nico, Gianluigi (Agricultural and Applied Economics Association, 2022)
African agriculture is highly sensitive to weather variability and extreme weather shocks. The question of how weather events affect participation in agricultural employment—including from a gender perspective—remains unanswered. This study aims to empirically quantify differences in how women and men adapt their participation in agricultural employment in response to climate variability and extreme weather events. Our study uses a novel individual-level database that draws mostly from Labour Force Surveys (LFS) that represents more than 80% of the total African population and covers nearly 86% of the Africa’s total workforce. In order to identify shock-affected areas, we match data from that LFS with gridcell monthly time series bioclimatic variables (temperature and rainfall). We estimate two systems of equations using the seemingly unrelated regressions (SUR) estimator to account for the potential contemporaneous correlation of the error terms in each equation. Descriptive results by region show that, regardless of age and sex, agriculture dominates employment distribution. In West and Central Africa and in East and Southern Africa region the agricultural sector employs the largest share of the working population. Multivariate SUR results show that, of all weather events, heat waves and droughts have the greatest detrimental effecton the intensity of individual efforts in agriculture; the number of work hours is reduced by 40% in the case of heat waves and 14% during droughts. If farmers are women, however, the reduction in work hours due to heat wave is lessened by 40%. Given the fundamental role of women both in agricultural production and in coping with extreme weather shocks, the key priorities would lie on implementation of sustainable, climate-resilient, and gender-sensitive policies; corresponding interventions in the labor market; and gender mainstreaming in planning and promoting agriculture- and job-related programs.